Draft Annual Plan 1988-89 Vol-I Introduction and GN Statements Government of Tripura - Planning Commission (Planning Commission, 1988)
It will be evident that in Agriculture and Allied Sector, the highest priority was attached to Crop Husbandry and till the third year of Seventh Five Year Plan it retains the sane importance. the objectives of increasing production for progressively scaling down dependence on other States could not be achieved till now to the desired extent.
Government of Tripura